A pilot study on the characterization and correlation of oropharyngeal and intestinal microbiota in children with type 1 diabetes mellitus - Wang, Limin; Gong, Chao; Wang, Ruiye; Wang, Jinxue; Yang, Zhanshuang; Wang, Xianhe (Frontiers in Pediatrics, 2024)
Background: Type 1 Diabetes Mellitus (T1DM) is one of the most common endocrine disorders of childhood and adolescence, showing a rapidly increasing prevalence worldwide. A study indicated that the composition of the oropharyngeal and gut microbiota changed in T1DM.However, no studies have yet associated the changes between the microbiomes of the oropharyngeal and intestinal sites, nor between the flora and clinical indicators. In this study, we examined the composition and characteristics of oropharyngeal and intestinal flora in patients with T1DM in compared to healthy children. We identified correlations between oropharyngeal and intestinal flora and evaluated their association with clinical laboratory tests in patients with T1DM.The oropharyngeal and fecal samples from 13 T1DM and 20 healthy children were analyzed by high-throughput sequencing of the V3-V4 region of 16S rRNA. The associations between microbes and microorganisms in oropharyngeal and fecal ecological niches, as well as the correlation between these and clinical indicators were further analyzed.: It was revealed that T1DM children had distinct microbiological characteristics, and the dominant oropharyngeal microbiota genus included Streptococcus, Prevotella, Leptotrichia, and Neisseria; that of intestinal microbiota included Blautia, Fusicatenibacter, Bacteroides, and Eubacterium_hallii_group. Furthermore, oropharyngeal Staphylococcus was significantly positively correlated with intestinal norank_f__Ruminococcaceae and Ruminococcus_torques_group in TIDM children. Moreover, in these children, differential genes in oropharyngeal and intestinal samples were enriched in metabolic pathways such as amino acid generation, fatty acid metabolism, and nucleotide sugar biosynthesis. Additionally, correlation analysis between the oropharyngeal/intestinal microbiome with laboratory tests showed significant correlations between several bacterial taxa in the oropharynx and intestines and glycated hemoglobin and C-peptide. Conclusion: Unique microbial characteristics were found in the oropharynx and intestine in children with T1DM compared to healthy children. Positive correlations were found between changes in the relative abundance of oropharyngeal and gut microbiota in children with T1DM.Associations between the oropharyngeal/intestinal microbiota and laboratory investigations in children with T1DM suggest that the composition of the oropharyngeal and intestinal flora in children with T1DM may have some impact on glycemic control.